Diversity of Foliar Endophytic Fungi in Artocarpus heterophyllus Lam. and Citrus reticulata Blanco of Tripura - Sanchita Bhattacharya; Sanjit Debnath; Ajay Krishna Saha (Journal of Tropical Life Science, 2021)
Present investigation dealt with the isolation and diversity of foliar fungal endophytes from two fruit yielding plants of Tripura state. Seasonal distributions of endophytes in respect to fruiting and non-fruiting season in two host plants were also studied. Twenty one fungal strains along with one nonsporulating hyaline form were isolated as foliar endophytes from the two host plants. In both fruiting and non-fruiting seasons, from Citrus reticulata seven foliar endophytic fungi were isolated. Whereas from Artocarpus heterophyllus in both the season eleven fungal endophytes with one nonsporulating hyaline form were isolated. The relative frequencies of isolated fungi from both A. heterophyllus and C. reticulata in fruiting and non-fruiting season significantly differed among the sampling sites, whereas relative frequencies individual endophytic fungus showed no significant differences among various sampling sites.